Cross-Cultural Learning Strategies for Entrepreneurship Education: Implications for Lifetime Education Towards Civil Society - Sonita, Era; Henmaid, Henmaidi; Nofialdi, Nofialdi; Anggraini, Resi (Journal of World Science, 2023)
Islamic universities have the belief and view that start-up activities create demand that will boost the economy. However, entrepreneurial activities have not developed in universities. This paper attempts to analyze the findings of a survey-based study of students receiving entrepreneurship education at IAIN Sjech M. Djamil Djambek Bukittinggi in West Sumatra. The main objective of this research is to compare management attitudes and students' attitudes towards entrepreneurship within the framework of cultural studies. Methodology/approach: using ratio measurement in quantitative research. For example, the sample will be asked to decide whether- those who are self-employed are seen as 1=failures, 2=not failures but also failures, 3=very successful. To ensure maximum reliability and validity, the questionnaire was administered in person. The Thurstone scale method with intervals used to evaluate quantitative research is the same. The results of the study show that the main difficulties in setting up and starting a business at UIN Sjech M. Djamil Djambek Bukittinggi are cultural and activity perceptions. Prospective Entrepreneurs/entrepreneurs who graduate from UIN Sjech M. Djamil Djambek Bukittinggi must build sustainable networks and relationships during and after creating a new business. Entrepreneurship education will be an important subject for Islamic tertiary institutions, so it is important to establish culturally adapted programs.